Analisis Determinan Pertumbuhan Ekonomi Beberapa Provinsi di Pulau Sumatera - Mifta Hul Rahman; Rahmat Daniel; Citra Uli; Hidayatulah Hidayatulah (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
This research aims factors contributing to economic growth in several provinces on Sumatra Island. Economic growth serves as an indicator reflecting the effectiveness of an economy, characterized by a significant increase in the production of goods and services. Key elements contributing to this growth include investment levels, workforce quality, infrastructure development, trade activities, as well as the fiscal and monetary policies implemented.Positive economic growth can be identified when the growth rate of Gross Domestic Product (GDP) exceeds the growth rate of the population, indicating beneficial effects on community welfare. The methodology used in this study is a quantitative approach, employing panel data analysis covering the period from 2009 to 2023, to investigate the impact of Foreign Direct Investment (FDI), Human Development Index (HDI), and inflation on economic growth.The analysis results show that FDI and inflation significantly influence economic growth, while HDI does not exhibit a meaningful impact. These findings provide strategic recommendations for regional development focused on achieving equitable and sustainable growth. This research also emphasizes the importance of implementing effective policies to enhance economic performance and improve the quality of life for communities in Sumatra.